Mengidentifikasi miskonsepsi mahasiswa pendidikan biologi pada konsep Bioteknologi Hewan - Hilarius Jago Duda; F Rahayu Esti Wahyuni; Antonius Edy setyawan (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: Many misconceptions are unknown to the instructor, so the instructor will not provide solutions for students who correct the misconceptions, of course this will improve the learning process as well as understanding students in the future on the concept. Therefore, researchers try to correct misconceptions that occur in students who have studied biotechnology courses on animal biotechnology concepts. Methods: The evaluation of the research was qualitative with qualitative descriptive methods. The study population was students of Biology Education STKIP Persada Equator Sintang, West Kalimantan and the sample used was 29 students. The technique of collecting data with multiple choice rounded tests and interviews. Data analysis using Certainty Of Response Index (CRI) and descriptive. Results: The research results obtained are misconceptions on the overall concept of animal biotechnology by 40.37%. From these data, quite a lot of biology education students have corrected misconceptions about the concept. The interview also concluded that students change misconceptions in addition to being caused by abstract concepts and many terms also related to information obtained previously from print media (such as books, journals), the internet, teaching staff, and peers. Conclusion: There are still many students who change misconceptions on animal biotechnology materials and are caused by print media, online, teaching staff and others. This research is useful for teaching staff to find out students' misconceptions and find solutions in overcoming the factors in overcoming the factors causing these misconceptions